From the editors - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
From the Editors RESEARCH ON NEW METHODS FOR TESTING LANGUAGE SKILLS: A FOCUS ON SPEAKING PERFORMANCE The current issue has speaking performance as a conducting thread, specifically, the research undertaken on new methods to test it. Testing language skills and defining the constructs under which tests need to be constructed is a complex task. Particularly, assessing speaking performance is a rather intricate process with many agents and variables involved and many factors affecting the final outcome. Subjectivity, fairness, anxiety, cognitive and metacognitive aspects, particular features of speech, individual abilities, and social constraints among others make the mastery of speaking in a foreign language and its subsequent assessment a definitely arduous task. Critical reflection and research on the part of educational institutions, researchers, test developers or any person undertaking assessment is of paramount importance to guarantee the adequacy, reliability and success of the whole testing process and results.